THE LEGAL NATURE OF SMART CONTRACTS PROGRAMMED USING BLOCKCHAIN TECHNOLOGY IN JORDANIAN LAW - Dr. Shadi Meeush Altarawneh (Scholar Express Journals, 2025)
Blockchain technology (Blockchain), or what is now known as the Internet of Transactions, is one of the technological solutions associated with the Fourth Industrial Revolution in the modern world. It is a secure cloud network through which transactions of various types are recorded, verified and executed. It is a chain of blocks that authenticate information that is created or modified electronically, and re-store and transfer that information. One of the areas that witnessed and kept pace with Blockchain technology is the conclusion of contracts and legal actions, and their implementation in an automated and automatic manner without the need for human intervention. So what are called smart contracts appeared, and the use of these electronic technologies in smart contracts requires a legal and regulatory framework, due to the modernity of this technology. This study includes an attempt to shed light on the legal nature of smart contracts using Blockchain
Keywords: Smart Contracts; Programmed Contracts; Blockchain Technology